Thermodynamic assessment of the stability of bulk and nanoparticulate cobalt and nickel during dry and steam reforming of methane - Wolf, Moritz (RSC Advances, 2021)
The high reaction temperatures during steam and dry reforming of methane inevitably entail catalyst deactivation. Evaluation of the feasibility or potentially relevant mechanisms at play is of utmost importance to develop highly active and stable catalysts. Herein, various oxidation reactions of bulk-sized nickel and cobalt to the corresponding metal oxide or in the presence of a metal oxide carrier are evaluated thermodynamically and linked to approximated conditions during methane reforming. In particular cobalt aluminate, as well as cobalt or nickel titanates are likely to form. As oxidation to bulk-sized metal oxide is unlikely, a thermodynamic analysis of metallic nanoparticles was performed to calculate the size dependent stability against oxidation to nickel oxide or cobalt oxide in water and carbon dioxide-rich environments. The calculations indicate that nickel nanoparticles >3 nm and cobalt nanoparticles >10 nm are expected to withstand oxidation during steam and dry reforming of methane with stoichiometric feed compositions and methane conversion levels >10% at temperatures up to 1100 and 900 °C, respectively. Lastly, the reduced thermal stability of nanoparticles due to melting point suppression was assessed, leading to similar recommendations concerning minimum particle sizes. This journal is
CRIS-Team Scopus Importer:2021-06-11